THE RELATIONSHIP OF CUSTOMER SATISFACTION AND SERVICE QUALITY TOWARDS CUSTOMER LOYALTY AT MHR BURGER’S DURING COVID-19 ENDEMIC - Nur Nilam Sari Mohd Basir; Yuary Farradia; Amran Harun (Yayasan Education and Social Center, 2022)
This paper aims to analyse the relationship of customer satisfaction and service quality toward customer loyalty at MHR Burger’s during Covid-19 endemic. Customer loyalty refers to a continuing emotional bond between you and your customer, manifested by a customer’s willingness to engage with and frequently purchase from you against your rivals. The main objectives of this study are to examine the relationship between customer satisfaction and services quality in MHR Burger’s during a Covid-19 endemic and secondly, to examine the mediator role of customer satisfaction between service quality and customer loyalty in MHR Burgers during a Covid-19 endemic. The variables involved in this study were perceived service quality, customer satisfaction, and customer loyalty. Samples of this study were customers of the MHR Burger’s restaurant in Malaysia. Quantitative method is used to analyse the relationships within variables. This research examined 250 respondents by spreading the online questionnaires that were analysed by using Structural Equation Model method. To collect the data, this study used convenience-sampling method. Study data were analyzed using SPSS software version 26 and Microsoft Excel. The results concluded that there is positive relationship between service quality with customer satisfaction and customer loyalty in which customer satisfaction has significant role as a mediator between service quality and customer loyalty at MHR Burger’s during Covid - 19 endemic